2018
DOI: 10.3390/catal8010027
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting Fe–Al Spinel Formation on a Narrowed Mesopore-Sized MgAl2O4 Support as a Novel Catalyst for H2 Production in Chemical Looping Technology

Abstract: Abstract:In this paper, the structure of Al 2 O 3 is modified with magnesium to synthesize MgAl 2 O 4 as an oxygen carrier (OC) support. The surface properties and structural stability of the modified support are improved by the incorporation of magnesium in the structure of the support and additionally by narrowing the pore size distribution (about 2.3 nm). Then, iron oxide is impregnated on both an

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 33 publications
(42 reference statements)
0
9
0
Order By: Relevance
“…Regarding Fe-based oxygen carriers, promoter materials such as Al 2 O 3 [78,79,80,81,82], MgO [83,130], TiO 2 [84,85,86], SiO 2 [87], MgAl 2 O 4 [88,89,90,91,103], CaO [92,93], ZrO 2 [94,95,96] and CeO 2 [22,97,98,99,100] have received extensive scientific attention in the past decades. However, these promoters can easily lead to solid-solid transformation with iron oxides during a continuous cycling process [127].…”
Section: Improvements To Oxygen Carriersmentioning
confidence: 99%
“…Regarding Fe-based oxygen carriers, promoter materials such as Al 2 O 3 [78,79,80,81,82], MgO [83,130], TiO 2 [84,85,86], SiO 2 [87], MgAl 2 O 4 [88,89,90,91,103], CaO [92,93], ZrO 2 [94,95,96] and CeO 2 [22,97,98,99,100] have received extensive scientific attention in the past decades. However, these promoters can easily lead to solid-solid transformation with iron oxides during a continuous cycling process [127].…”
Section: Improvements To Oxygen Carriersmentioning
confidence: 99%
“…[ 7,12,13 ] However, since iron oxide and alumina can form spinel structures at high temperatures, which limits the reduction of oxygen carriers, it is important to improve the reduction kinetics of oxygen carriers. [ 12,14 ] Some studies have reported the use of the self‐diffusion characteristics of alkali metals to improve the reduction kinetics of the OCs. [ 7,13,15,16 ] However, alkali metals volatilize and deactivate at high temperatures, which prevents the oxygen carrier from being reused in multiple cycles and corrodes the reactor.…”
Section: Introductionmentioning
confidence: 99%
“…[18]), H 2 evolution [25], and CO 2 reduction [26,27]. Six other papers focus on conventional catalysis ("dark" reactions), reporting efficient H 2 production [28,29], synthesis of ethanol and butanol [30], direct conversion of CO 2 and methanol to dimethyl carbonate [31], water purification [32], and advanced characterization of catalysts by X-ray absorption fine structure (EXAFS) spectroscopy [33]. The majority of studies have been performed with particulate catalysts (nanoparticles (NPs)), but organized nanostructures, such as nanotubes (TiO 2 /Cu x O y [18], carbon nanotubes (CNTs) [30,32]) and nanowires (CeO 2 [31]) have also been used.…”
mentioning
confidence: 99%
“…They found that the surface reduction under H 2 atmosphere formed acidic/alkaline sites on the catalyst surface, and thus significantly improved catalytic activity, reducing the activation energy barrier from 74.7 to 41.9 kJ/mol. Complex catalytic studies were performed by Hafizi and Rahimpour for catalytic H 2 production [28]. The effect of alumina and Mg-Al spinel as the support for the formation of Fe 2 O 3 catalyst was investigated.…”
mentioning
confidence: 99%